The Effect Of The Use Of Traditional Congklak Games On Initial Numeracy Ability And Interest In Learning In Children Aged 5-6 Years - Mauizatul Marhamah; Muthmainah Muthmainah; Bafirman Bafirman; Fiky Zarya (Postgraduate, University of Mataram, 2024)
Efforts to form a character and children's knowledge have a variety of specific modifications, one of which is traditional games. In addition to introducing ancestral sports to early childhood, it can be used as a learning resource to be able to improve numeracy skills and learning interests that are not relatively monotonous. This study aims to find out (1) The effect of the use of traditional game congklak in on the ability to count early in children aged 5-6 years. (2) The effect of the use of traditional games on learning interest in children aged 5-6 years. (3) The significant influence of the use of traditional congklak games on early numeracy ability and interest in learning in children aged 5-6 years. This study is a quasy experiment study with a nonequivalent control group design, the population of this study is all group B children after 5-6 years at Kindergarten IT Uswatun Hasanah and Kindergarten Nur Rabbi Palembang, with a sample of 60 children. The instruments used were in the form of observation techniques for initial numeracy skills and learning interests of children aged 5-6 years. The data analysis technique used independent sample t-test analysis with a significance level of 0.05. The results of the study showed that: (1) There was a significant influence of the traditional game of congklak on the initial numeracy ability of children aged 5-6 years where the results of the paired sample t-test were obtained on average of 153.47 with a Sig value of 0.000 < 0.05. (2) There was a significant influence of traditional congklak games on the learning interest of children aged 5-6 years where the results of the paired sample t-test were obtained on average of 443.07 with a Sig value of 0.000 < 0.05. (3) There was a significant influence of traditional congklak games on the initial counting and learning interest of children aged 5-6 years where the test results of the t-test (Independent Sample Test) with a Sig value of 0.000 < 0.05. Based on the study, it can be concluded that there is a significant influence on the traditional game of congklak on the initial numeracy ability and interest in learning in children aged 5-6 years.